Evaluation of a telementalhealth alcohol use intervention program for mandated college students - Parker, Lauren (Journal of addictions & offender counseling, 2025)
The Youthful Offenders Program for Telementalhealth (YOP-T) is a synchronous brief intervention for alcohol harm reduction and the virtual application of the Youthful Offenders Program. This study aims to provide psychometric support for use of the protective behavioral measurements Safe Drinking Practices and Avoid Risky Behaviors in telementalhealth and to provide preliminary evidence for the effectiveness of YOP-T in eliciting alcohol use and related harm reductions and increases in protective strategy utilization (N = 302). Reliability and validity for measurements were observed, and preliminary support for program effectiveness was established. Recommendations to improve psychometric properties and generalizability are discussed.